Development of edge finder - Noraini, Mat Daud (2013)
EDGE FINDER is a tool used to accurately determine edges or markings and therefore the center of a workpiece or a previously machined feature during the set-up phase of a machining operation. The electronic circuit has been designed to develop the Electronic Edge Finder. The electronic circuits contains of two magnetic wire probes when connected between the vise and the spindle of the milling machine. The Electronic Edge Finder is connected directly to the tool and spindle on the milling without any modification to the machine. It is detect the changes of the electrical resistance of the machine when there are contact between the workpiece and the tool. It is then to use to setting up the workpiece zero point by referring to the light of the LED on the Electronic Edge Finder circuit. At the end of the project, the Electronic Edge Finder is developed and can be used to setup the tool and marked the zero point on the workpiece.